Long-term functional outcome after dorsal capsular imbrication for post-traumatic dorsal instability of the distal radioulnar joint - Unglaub, Julia Marie; Heyse, Thomas; Bruckner, Thomas; Langer, Martin Franz; Spies, Christian (International orthopaedics, 2020)
The goal of this study was the assessment of long-term outcome of dorsal capsular imbrication of the distal radioulnar joint (DRUJ) in dorsal instability.
Gesehen am 16.02.2025